MENINGKATKAN MINAT MEMBACA DAN HASIL BELAJAR PESERTA DIDIK MELALUI MEDIA KOMIK - Suradin; Meirza Nanda Faradita; Iswahyuni (PROCEEDING UMSURABAYA, 2024)
Interactive and interesting learning media has great potential to stimulate learners to respond positively to the learning material presented.comics are one of the interesting learning media for students. This study aims to increase students' interest in reading and learning outcomes through Comic media in Indonesian language subjects of non-fiction text material in class V SD Juara Surabaya. The results of the analysis obtained, students' interest in reading increased from pre-cycle 55, cycle I 81. 25 and in cycle II 87. 50. The ability to analyse the reading of students increased from pre-cycle 55, cycle I 83 and cycle II 89.